Are Activation Teaching Methods Really Effective? - Gabriela Gabrhelová; Slávka Čepelová (HighTech and Innovation Journal, 2022)
The primary aim of the presented paper is to demonstrate the effectiveness of activation teaching methods in the teaching of technical subjects at secondary vocational schools through pedagogical research using a pedagogical experiment. The effectiveness of the activation teaching methods is demonstrated in the Integrated Rescue System subject taught in the field of Security and Legal Activity. The object of the research are pupils who were 2nd year pupils in the 2019/2020 school year, as well as teachers of the analyzed subject. The pedagogical experiment was carried out in three consecutive years, namely in the school years 2019/2020, 2020/2021 and 2021/2022. The presented paper has the classic structure of a scientific work; it is divided into a theoretical and an analytical part. We processed the theoretical part of the work using secondary analysis. Pedagogical research was used in the analytical part of the work. Both qualitative and quantitative pedagogical research were used. Qualitative pedagogical research was carried out using a semi-structured interview with open questions. Observation was also used. The quantitative part of the pedagogical research was carried out using a standardized questionnaire. Another method of quantitative pedagogical research was the pedagogical experiment, i.e., its implementation led to obtaining outputs of a quantitative nature. When evaluating the results of pedagogical research of a quantitative nature, we used mathematical-statistical methods for our chosen variables, which were not only processed, but also analyzed through the statistical program SPSS Statistics 22.0. We proved through a pedagogical experiment of a longitudinal nature that activation teaching methods are really effective in teaching technical subjects at secondary vocational schools, while within the framework of that pedagogical experiment it was proved that it is possible to apply activation teaching methods very effectively in the so-called flipped classroom model, which we present as suitable for effective activation teaching of secondary school pupils.